2021 ACC/AHA/SCAI Guideline for Coronary Artery Revascularization: Executive Summary: A Report of the American College of Cardiology/American Heart Association Joint Committee on Clinical Practice Guidelines. Issue 3 (9th December 2021) - Lawton, Jennifer S.; Tamis-Holland, Jacqueline E.; Bangalore, Sripal; Bates, Eric R.; Beckie, Theresa M.; Bischoff, James M.; Bittl, John A.; Cohen, Mauricio G.; DiMaio, J. Michael; Don, Creighton W.; Fremes, Stephen E.; Gaudino, Mario F.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Aim: The executive summary of the American College of Cardiology/American Heart Association/Society for Cardiovascular Angiography and Interventions coronary artery revascularization guideline provides the top 10 items readers should know about the guideline. In the full guideline, the recommendations replace the 2011 coronary artery bypass graft surgery guideline and the 2011 and 2015 percutaneous coronary intervention guidelines. This summary offers a patient-centric approach to guide clinicians in the treatment of patients with significant coronary artery disease undergoing coronary revascularization, as well as the supporting documentation to encourage their use. Methods: A comprehensive literature search was conducted from May 2019 to September 2019, encompassing studies, reviews, and other evidence conducted on human subjects that were published in English from PubMed, EMBASE, the Cochrane Collaboration, CINHL Complete, and other relevant databases. Additional relevant studies, published through May 2021, were also considered. Structure: Recommendations from the earlier percutaneous coronary intervention and coronary artery bypass graft surgery guidelines have been updated with new evidence to guide clinicians in caring for patients undergoing coronary revascularization. This summary includes recommendations, tables, and figures from the full guideline that relate to the top 10 take-home messages. The reader is referred to the full guideline for graphical flow charts, supportive text, and tables with additional details about the rationale for and implementation of each recommendation, and the evidence tables detailing the data considered in the development of this guideline.